The economics of natural gas: pricing, planning and policy - Julius, DeAnne; Mashayekhi, Afsaneh; Oxford Institute for Energy Studies (Oxford : Oxford University Press for the Oxford Institute for Energy Studies, 1990)
Addressing the issue of how the "economic price" of gas is determined, this text examines estimates of the costs of exploration and production of gas, and also lists the benefits to be derived from its use in various economic sectors for a number of Third World countries. R
Includes index
oif 22/07/16
Loans
Keywords: Petroleum industry and trade; Gas industry